An amorphous hierarchical MnO2/acetylene black composite with boosted rate performance as an anode for lithium-ion batteries. Issue 31 (20th July 2021) - Zhang, Xiaole; Li, Song; Wang, Shenghe; Wang, Zhenxu; Wen, Zhongsheng; Ji, Shijun; Sun, Juncai
Abstract : An amorphous hierarchical MnO2 /AB composite prepared via a ball-milling method exhibited excellent coulombic efficiency and rate performance. Abstract : Amorphization is considered to be an effective way to enhance the electrochemical performances of electrode materials due to the existence of isotropy and numerous defects. Herein, an amorphous hierarchically structured MnO2 /acetylene black (a-MnO2 /AB) composite is successfully fabricated via a redox method and subsequent mechanical ball milling. The a-MnO2 /AB composite is composed of approximately 300 nm flower-like amorphous MnO2 submicron spheres and acetylene black particles with a diameter of about 50 nm. The a-MnO2 /AB electrode exhibits an initial coulombic efficiency of 73.2%, excellent rate capabilities of 318 mA h g −1 at 9.6 A g −1, and high specific capacity retention of 1300 mA h g −1 after 300 cycles at 1 A g −1 . The amorphous structure can provide more channels for rapid lithium-ion transmission due to the disorder and defects, and the ion-diffusion coefficient (∼5 × 10 −7 cm 2 s −1 ) is higher than those of crystalline materials. Due to the strong interactions (Mn–O–C bonds) between MnO2 and AB as a result of the ball milling, the composite shows low charge transport resistance and small volume changes during the discharging/charging process. This work provides a facile route for the construction of amorphous hierarchically structured Mn-based oxides as anodes for lithium-ion batteries (LIBs).